Gracilaria spp. morphology cultured in brackish water pond Pantai Sederhana Village, Muara Gembong - Soelistyowati, Dinar Tri; Murni, Ida Ayu Amarilia Dewi; Wiyoto (Jurnal Akuakultur Indonesia, 2014)
ABSTRACT Gracilaria spp. is a euryhaline species of seaweed which can live in the marine and brackish water. Development of Gracilaria spp. culture in Bekasi is potential because this seaweed can be cultured in ex shrimp pond by polyculture system. The objective of this research was to evaluate the phenotype morphological characteristic of Gracilaria spp. based on and its relationship with shrimp pond water quality. Sampling was done at three shrimp ponds with a salinity range at 13.7–19.2 g/L. Phenotypical characteristics of Gracilaria spp. consisted of colour and thallus morfometrics, while measurement of water quality consisted of physical and chemical charactersof shrimp pond. The result showed that Gracilaria spp. generally had light brown colour. At salinity higher than 13.7 g/kg, the number of secondary thalli increased, the distance among internode tertiary thalli declined, and the number of ramification index increased. Salinity showed a positive correlation with remification index which was 0.571. Keywords: Gracilaria spp., remification index, phenotype, salinity, brackishwater culture  ABSTRAK Gracilaria spp. merupakan spesies rumput laut eurihalin yang dapat hidup di laut dan di perairan payau. Pengembangan budidaya Gracilaria spp. di Bekasi potensial dilakukan karena memanfaatkan tambak bekas budidaya udang dengan sistem polikultur. Penelitian ini bertujuan untuk mengevaluasi karakteristik fenotipe morfologi Gracilaria spp. dan hubungannya dengan kualitas air di tambak budidaya. Sampling dilakukan pada tiga tambak dengan kisaran salinitas 13,7–19,2 g/L. Karakterisasi fenotipe meliputi warna dan morfometrik talus Gracilaria spp., sedangkan parameter kualitas air meliputi karakter fisika dan kimia air tambak. Hasil menunjukkan talus Gracilarias spp. umumnya berwarna coklat muda dan pada salinitas di atas 13,7 g/L menunjukkan jumlah talus sekunder meningkat, jarak internode talus tersier menurun, dan indeks percabangan meningkat (P<0,05). Salinitas berkorelasi positif dengan indeks percabangan sebesar 0,571. Kata kunci: Gracilaria spp., indeks percabangan, fenotipe, salinitas, budidaya air payau